The Effect of Special Exercises Using Isometric Style and Aiding Devices For Rehabilitating Thigh Muscle Atrophy in Soccer Players After Surgical Intervention Of Anterior Cruciate Ligament - Muhsin, Mustafa; Mohammed, Ahmed (Journal of Physical Education, 2019)
The research aimed at designing rehabilitation exercises using isometric static contraction style with rubber band and weightlifting equipment’s on soccer primer league player to improve muscular strength and rehabilitating ACL injury. The problem of the researcher lied in ACL being a common injury in soccer that require long period of treatment and rehabilitation. The researchers used the experimental method on (3) ACL soccer players who have thigh muscle atrophy. The researchers conclude that using isometric style, rubber bands, and bodybuilding equipment have an effective role on improving muscular strength and treating muscle atrophy.